Reframing democratic legitimacy and public accountability: an interdisciplinary analysis of DPRD-based regional head elections in Indonesia - Teguh Purnomo; Uswatun Khasanah (Institute of Computer Science (IOCS), 2026)
Studies on regional head elections in Indonesia have predominantly examined either the constitutional legality of direct and indirect electoral mechanisms or their political implications for democratic participation and governance stability. However, limited attention has been given to the interdisciplinary relationship between constitutional legitimacy and public accountability within the Regional People’s Representative Council (DPRD)-based regional head election system. This study addresses this gap by integrating constitutional law and public administration perspectives to analyze how indirect regional head elections shape democratic legitimacy, accountability patterns, and local governance structures in Indonesia. Using a normative juridical method with a qualitative analytical approach, this study examines constitutional provisions, statutory regulations, Constitutional Court interpretations, and relevant scholarly literature. The findings demonstrate that the DPRD-based election mechanism possesses constitutional legitimacy under Article 18 paragraph (4) of the 1945 Constitution, which adopts the phrase “democratically elected” and allows both direct and indirect electoral models as part of an open legal policy framework. Nevertheless, the study reveals that procedural constitutional legitimacy does not automatically ensure substantive democratic legitimacy. The indirect electoral mechanism shifts accountability from citizens to legislative institutions, strengthens legislative dominance within local political structures, and increases the potential for elite bargaining and transactional politics. The study further argues that the quality of representative institutions becomes the decisive factor in determining whether indirect elections can maintain democratic accountability and effective governance. Theoretical contributions of this study include the development of an interdisciplinary analytical framework linking procedural democracy, constitutional interpretation, and institutional accountability in decentralized governance systems. Practically, the study provides critical insights for policymakers regarding the constitutional and governance